Job Satisfaction as a Mediator between Humanistic Employee Management and Service Quality in the Hotel Industry - Kalsum, ER Ummi; Rahmawati, Rahmawati; Afriza, Lia; Isma, Andika (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study examines the effect of humanistic employee management on service quality through job satisfaction in the Rooms Division of four-star hotels in Greater Bandung. In the hospitality industry, service quality depends not only on operational efficiency but also on how employees are managed and supported. Using a quantitative approach, survey data were collected from Rooms Division employees and analyzed with Structural Equation Modeling (SEM) to test the direct and indirect relationships among the variables. The results show that humanistic employee management has a significant positive effect on both job satisfaction and service quality. Job satisfaction also significantly influences service quality and partially mediates the relationship between humanistic employee management and service quality. These findings indicate that employee-centered management practices contribute to better employee attitudes and more consistent service performance. The study highlights the importance of humanistic management in high-contact hotel operations, particularly in Front Office and Housekeeping, where employee well-being and service delivery are closely interconnected.